2021
DOI: 10.3390/app11041496
|View full text |Cite
|
Sign up to set email alerts
|

Composting Hydrochar-OFMSW Digestate Mixtures: Design of Bioreactors and Preliminary Experimental Results

Abstract: An increasing number of industrial plants integrate the anaerobic digestion (AD) of the organic fraction of municipal solid waste (OFMSW) with a subsequent composting phase. To improve the plant productivity, a fraction of OFMSW digestate can be converted into a carbonaceous material, called hydrocar (HC), through Hydrothermal Carbonization (HTC), and then composted together with the OFMSW digestate itself, to produce “hydrochar co-compost”. The aim of this paper is to present the design and assembly of batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The solid product derived from HTC, also known as hydrochar, has been demonstrated to attain benefits when added as a supplement in anaerobic digestion and composting, similar to those reported by biochar obtained from pyrolysis processes [37][38][39][40][41][42]. Other reports have also demonstrated that char may act as an active compound, improving nutrient management in crops [43,44].…”
Section: Introductionmentioning
confidence: 55%
“…The solid product derived from HTC, also known as hydrochar, has been demonstrated to attain benefits when added as a supplement in anaerobic digestion and composting, similar to those reported by biochar obtained from pyrolysis processes [37][38][39][40][41][42]. Other reports have also demonstrated that char may act as an active compound, improving nutrient management in crops [43,44].…”
Section: Introductionmentioning
confidence: 55%
“…After some mathematical steps [35], and after imposing 1 − ∆v/(∆v ∞ ) = Φ(E, T) ∼ = 0.58, the representative equation of the Miura-Maki model is given by Equation (13).…”
Section: Miura-maki Modelmentioning
confidence: 99%
“…This was found in the range of α 0.1-0.8 for pyrolysis and 0.1-0.9 for oxidation. Then, for the valid range of α, E and k 0 were determined graphically using the schemes in Figure 7; E is given by the slope of each line for each α, while k 0 is obtained from the intercept and by applying Equation (13). Under pyrolysis, the fitting is satisfactory, with a R 2 always higher than 0.95, except for one outlier at α = 0.7 for the 220 • C hydrochar.…”
Section: Miura-maki Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the process of hydrothermal carbonization also removes a part of the inorganic fraction of biomass [54,55]. Hydrothermal carbonization also has an influence on the morphology of the hydrochars [56,57], and, as a consequence, makes the latter a good precursor for the production of activated carbon [58,59] and also for direct application to soil or compost [60,61]. Furthermore, positive influence of the HTC process on biomass grindability should not be overlooked, as particle size is an important aspect of pyrolysis [62][63][64].…”
Section: Introductionmentioning
confidence: 99%